Modelling the mechanical response of cellular PVC foams using detailed nite element analysis - Berg, Rikard; Billberg, Adam (My University, 2019)
The use of composites with a foam core is becoming more and more common as industries strive to make lighter structures. However, the mechanical response of cellular foams is hard to model properly due to its complicated microstructure and deformation mechanisms. Previous work in the eld of modelling cellular foams have focused on capturing the yield surface using both advanced material models and by modelling the microstructure of the foam. The current study aims at capturing the macroscale stress-strain response during uniaxial tension, compression, and shear loads by performing analyses on a geometry representing the foam microstructure. Two foams are investigated in the current study; Divinycell H60 and H100, manufactured by Diab. The Kelvin tetrakaidecahedron was used to represent the foam microstructure of a single cell. The e ciency of the simulations were greatly enhanced by the use of a Representative Volume Element (RVE) with Periodic Boundary Conditions (PBC) to emulate an in nitely large foam under constant average strain using a single foam cell. This allowed for calibration of key parameters through an iterative process, with the aim to capture the mechanical response for one of the investigated foams, Divinycell H100. Experimental results from the remaining foam, Divinycell H60, was then used to validate the derived parameters without a separate optimisation procedure. The study found that an RVE can be used to accurately model the initial mechanical response of foam in both the elastic and plastic region. By optimising material and geometric parameters for the H100 foam, the elastic region was captured well for both tension and shear in two principal directions. Furthermore, the compressive behaviour in the elastic region and the initial phase of buckling was captured in two principal directions. By using the same material parameters and re-scaling the geometric parameters, good correlations to the experimental data was achieved also for H60. Due to the progressive crushing at large compressive strains, cellular foams do not behave periodically in the direction of the load. This makes it impossible to capture the full true deformation mechanisms using full PBC's, since they imply that the material behaves periodically in all directions.
Keywords: PVC Foam; Representative Volume Element; Periodic Boundary Conditions; Finite Element Analysis; Divinycell; Microstructure